2021
DOI: 10.3389/fpsyg.2021.689407
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotion Differentiation Predicts Psychotherapy Outcome: Preliminary Findings

Abstract: Emotion differentiation (ED), the extent to which same-valenced emotions are experienced as distinct, is considered a valuable ability in various contexts owing to the essential affect-related information it provides. This information can help individuals understand and regulate their emotional and motivational states. In this study, we sought to examine the extent to which ED can be beneficial in psychotherapy context and specifically for predicting treatment response. Thirty-two prospective patients with moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Especially, emotion decoding abilities may be clinically meaningful to target in the treatment of MDD. A study by Lazarus and Fisher (2021) found that individuals who displayed good emotion decoding abilities generally had better outcomes of psychotherapy. Thus, improving the identified emotion decoding problems in MDD patients with childhood maltreatment may potentially benefit their treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, emotion decoding abilities may be clinically meaningful to target in the treatment of MDD. A study by Lazarus and Fisher (2021) found that individuals who displayed good emotion decoding abilities generally had better outcomes of psychotherapy. Thus, improving the identified emotion decoding problems in MDD patients with childhood maltreatment may potentially benefit their treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, by applying both HLM and RI-CLPM to these data, these results can function as a second empirical replication of Falkenström et al's (2022) results. By testing both lag-1 and contemporaneous effects, we hope to help future researchers specify the timescale at which these theorized processes occur (Fisher & Bosley, 2020;Lazarus & Fisher, 2021), since these are currently unknown. Both anxiety (OASIS), B = -.30, SE = .07, p < .01, 95% CI [-.43, -.17], d = .53, and depression (ODSIS), B = -.42, SE = .08, p < .01, 95% CI [-.59, -.26], d = .65, significantly decreased across the first seven sessions/weeks (see Table 1 for means and standard deviations at each session).…”
Section: Data Analytic Methodsmentioning
confidence: 99%
“…Differentiation scores are computed by reverse-scoring the intraclass correlation of these ratings: High correlations between these ratings indicate that people essentially use all of these emotion words identically, whereas low correlations indicate that they think of each as a unique emotional experience. Emotion differentiation scores have now been widely associated with healthy emotion regulation (Barrett et al, 2001;Kalokerinos et al, 2019), mental health in both youth and adults (Demiralp et al, 2012;Nook, 2021;Nook, Flournoy, et al, 2021;O'Toole et al, 2020;Seah & Coifman, 2022), and even treatement response (Lazarus & Fisher, 2021). However, unlike our other constructs reviewed here, emotion differentiation does not currently have a purely linguistic measure.…”
mentioning
confidence: 94%